Clinical feasibility of the therapeutic strategies total neoadjuvant therapy and “watch and wait” in the treatment of rectal cancer patients with recurrence after clinical complete response - Dai, Dianyin; Liu, Ge; Liu, Huanran; Liu, Yanfeng; Liu, Xinlu; Li, Shuang; Lei, Yanan; Gao, Yun; Wang, Yuezhu; Zhang, Shoujia; Zhang, Ran (Frontiers in Surgery, 2023)
Purpose: In recent years, total neoadjuvant therapy (TNT) has emerged as a new therapeutic strategy against advanced rectal cancer (RC). After administration of TNT, some patients show complete clinical response (cCR) to treatment however, disputes about the effects of TNT and the alternative treatment plans in case of recurrence after cCR still exist. Methods: A total of 100 patients were included in this paper. CR and non-CR was observed when these patients were administered with TNT at the First Affiliated Hospital of Dalian Medical University, China from May 2015 to June 2021. These patients received different chemotherapeutic regimens, with close monitoring and watch and wait (W&W) strategy being applied by a multidisciplinary team (MDT). According to treatment results, patients were divided into a cCR group and a non-cCR group; according to the recurrence during W&W, they were divided into a recurrence group and a no-local-recurrence group. This study analyzed the factors that may affect the prognosis, and summarized the surgery and treatment after recurrence. Results: The TNT strategy was effective, and 85% of patients achieved local remission. However, W&W did not affect the survival time of CR patients, nor did it cause new distant metastasis due to local recurrence during the observation period (P > 0.05). However, for patients with positive CRM, we do not recommend W&W as the first choice of treatment (P < 0.05). Conclusion: 1. Whole-course neoadjuvant therapy was an effective treatment scheme for advanced mid-term rectal cancer. The total local reduction rate of this group of cases was 85.00%, meaning that 25 patients achieved CR. 2. W&W was safe and reliable, and CR patients could receive it as the preferred treatment. 3. CRM was an independent risk factor for local recurrence in CR patients. We do not recommend W&W as the preferred treatment for CR patients with positive CRM. Keywords: Total neoadjuvant therapy; rectal cancer; watch and wait; local recurrence, circumferential resection margin.